Impact of contractor competitiveness on firm performance: a view from real estate developers - Pongpeng, Jakrapong; Rojanathamwong, Waiwit; Peansupap, Vachara (My University, 2026)
While previous studies have identified contractor competitiveness factors as selection criteria, few have empirically examined how these factors influence firm performance. This gap limits developers’ ability to select criteria for contractor selection. This study aims to analyze the impact of contractor competitiveness on performance and investigate the underlying influencing factors. A comprehensive literature review was employed to develop a conceptual model. Data were collected through a questionnaire survey of Thai real estate developers. Structural Equation Modeling (SEM) was applied to evaluate the proposed model and test research hypotheses, thereby addressing the gap in understanding the contractor competitiveness’s role in organizational success. The SEM analysis revealed a significant positive relationship between contractor competitiveness and performance (standardized regression weight = 0.65). Moreover, the factors influencing contractor competitiveness include management, resources, and generic competitive strategies, with regression weights of 0.99, 0.76, and 0.76, respectively. This study offers theoretical contributions to research on contractor competitiveness. First, the conceptual model elucidates the impact of contractor competitiveness on firm performance from the perspective of real estate developers. Second, the model confirms the hypothesis that management, resources, and generic competitive strategies measure contractor competitiveness. Furthermore, these findings provide developers that assessing contractor competitiveness directly improves firm performance.
Keywords: Contractor competitiveness; contractor firm performance; real estate developer; Structural Equation Modeling (SEM)